Dinamika Sekuritisasi Isu Keamanan dalam Perkembangan Industri PSMC Afrika Selatan vis-a-vis Regulasi Pembatasan Pemerintah - Akhmad Hani Nadif; Probo Darono Yakti (Jayapangus Press, 2022)
This reaserach is about the 1998 RFMA Act and the establishment of a new PSMC company namely STTEPI in 2006. In 1989, South Africa experienced a period of emergency due to a major event that caused political instability in South Africa and its surroundings. The apartheid government carried out securitization to overcome these problems by establishing a security agency that took coercive actions on the security of the state and the ruling regime. After the process of transition of power, a new government was applied to the PSMC. On the other hand, in 2006 a new PSMC company was established. The research aims to answer the question how can the formation of bodies and restrictions that limit PSMC's movements, the PSMC industry continue to develop? In answering, concepts such as: (1) securitization are used to explain the emergence of the PSMC industry in South Africa; and (2) the concept of power; as well as (3) the national political image to describe the PSMC-government relationship which was analyzed using qualitative-descriptive methods from literature studies on primary sources from the government and secondary sources from scientific journal articles and news. It was found that in the application of regulations, the NCACC and PSIRA indicated that there were gaps in operating permits and having permits. There is interference from the PSMC in the government agency. This is compounded by the weaknesses of regulations which in their application are indicated to be poorly enforced. This study resulted in a conclusion that there was a complex relationship between industrial defense (PSMC) and the South African government due to major political changes and instability in regional political and security conditions that were used in omission actions in order to make losses and maximize opportunities for the country's economic interests